Potential of near-infrared fluorescence image-guided debridement in trauma surgery - Pruimboom, Tim (Case Reports Plast Surg Hand Surg, 2018)
This case report presents the use of near-infrared fluorescence (NIRF) imaging using indocyanine green (ICG) and its potential for the evaluation of soft tissue viability in a traumatic case. Standard implementation of this novel imaging modality might decrease the number of surgical debridement procedures in complex traumatic wounds.